Improving Students' Communication Capability in Interacting with Medical Personnel, Patients and Families During Clinical Nursing Practice Through Asertive Communication Socialization: Peningkatan Kemampuan Komunitasi Mahasiswa Dalam Berinteraksi Dengan Tenaga Medis, Pasien dan Keluarga Selama Praktik Klinik Keperawatan Melalui Komunikasi Asertif (AgroNurse Kesehatan : Jurnal Pengabdian Masyarakat, 2023)
Students in the late adulthood crisis age easily experience confusion due to life changes and also preparations for the future. When students have to adapt to new environments and responsibilities, they need soft skills and support systems to be able to use adaptive coping. Support through socialization of assertive communication is an effort to improve students' communication skills in interacting with medical personnel, patients and families during nursing clinical practice. The general aim of this community service activity is that after socialization it can improve students' personal abilities in communicating in practical areas and in the social life of the community. The method used is socialization regarding assertive communication strategies to students. The results obtained showed that the socialization of students' communication skills and knowledge regarding how to interact increased after taking part in the socialization.